2008
DOI: 10.1063/1.2979703
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the output and efficiency of a high power cascaded arc hydrogen plasma source

Abstract: The operation of a cascaded arc hydrogen plasma source was experimentally investigated to provide an empirical basis for the scaling of this source to higher plasma fluxes and efficiencies. The flux and efficiency were determined as a function of the input power, discharge channel diameter, and hydrogen gas flow rate. Measurements of the pressure in the arc channel show that the flow is well described by Poiseuille flow and that the effective heavy particle temperature is approximately 0.8 eV. Interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 19 publications
5
79
1
Order By: Relevance
“…At sufficiently high electron densities these H * are susceptible to being reionized leading to larger electron densities. This has been observed by Veremiyenko et al [27] and Vijvers et al [14] and confirmed by our measurements (see Fig. 11).…”
Section: Effect Of the Arc Currentsupporting
confidence: 82%
See 1 more Smart Citation
“…At sufficiently high electron densities these H * are susceptible to being reionized leading to larger electron densities. This has been observed by Veremiyenko et al [27] and Vijvers et al [14] and confirmed by our measurements (see Fig. 11).…”
Section: Effect Of the Arc Currentsupporting
confidence: 82%
“…They reported electron densities on the order of a few times 10 20 m −3 . Vijvers et al [14] have performed Thomson scattering on magnetized hydrogen plasmas measuring n e up to 9 × 10 21 m −3 with a magnetic field of 200 mT. Research conducted by van Rooij et al [15] and electron temperatures up to 3.0 eV.…”
Section: Introductionmentioning
confidence: 99%
“…15. A so-called cascaded arc source 16,17 creates a plasma, which exhausts into the vacuum vessel along the magnetic field axis. A strong axial magnetic field confines the plasma, generating an intense magnetized cylindrical plasma beam.…”
Section: à3mentioning
confidence: 99%
“…1a and is described in more detail in [38,39]. In our experiments, a hydrogen plasma was generated by a cascaded arc plasma source [40] and expanded into a downstream vessel along a magnetic field of 0.4-0.8 T generated by electromagnetic field coils. The radially resolved plasma parameters were measured by a Thomson scattering system [41] 2.7 cm in front of the sample and show a typically high central electron density (>10 20 m -3 ) and an electron temperature of 1-2 eV.…”
Section: Synthesis and In Situ Diagnosticsmentioning
confidence: 99%